1994
DOI: 10.1079/bjn19940144
|View full text |Cite
|
Sign up to set email alerts
|

Improved nitrogen metabolism in rats fed on lipid-rich liquid diets

Abstract: N metabolism was studied in young rats fed on lipid-rich, isonitrogenous, purified liquid diets, a convenient and easy technique for inducing voluntary overfeeding of energy and lipids under controlled nutritional conditions. Overfed rats showed a marked N retention at the expense of a reduced production of urea. The capacities of isolated hepatocytes to synthesize urea and glucose from added precursors were greatly diminished. The activities of the urea cycle enzymes and several enzymes involved in the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The marked N 2 retention was due to a decrease in amino acid catabolism and in urea production by the liver (Sadhu, 2010). Therefore daily N 2 retention was greatly enhanced in these animals which is in agreement with the known protein-sparing effect of fat (excess dietary fats spare or retain the body protein) (Estornell et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…The marked N 2 retention was due to a decrease in amino acid catabolism and in urea production by the liver (Sadhu, 2010). Therefore daily N 2 retention was greatly enhanced in these animals which is in agreement with the known protein-sparing effect of fat (excess dietary fats spare or retain the body protein) (Estornell et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, OLE supplementation increased plasma urea concentration. High-fat diet feeding decreased urea synthesis in rats (35,36) due to reduced activities of all the enzymes of the urea cycle (35). These results along with improved glucose metabolism indicate that OLE attenuated the diet-induced metabolic deterioration.…”
Section: Discussionmentioning
confidence: 67%
“…More importantly, L. stoechas supplementation, protected against alloxan-induced decrease of plasma uric acid concentration as one of the major endogenous water-soluble antioxidants [49], as well as tissue malondialdehyde increase, as marker of lipid peroxidation [50]. We also showed that alloxan administration decreased antioxidant enzymes activities such as SOD and CAT.…”
Section: Discussionmentioning
confidence: 69%